2021
DOI: 10.1109/access.2021.3133572
|View full text |Cite
|
Sign up to set email alerts
|

Design of Capacitorless DRAM Based on Polycrystalline Silicon Nanotube Structure

Abstract: In this study, a capacitorless one-transistor dynamic random-access memory (1T-DRAM) based on a polycrystalline silicon nanotube structure with a grain boundary (GB) is designed and analyzed using technology computer-aided design (TCAD) simulation. The proposed 1T-DRAM has the improved electrical performances because the outer gate (OG) and the inner gate (IG) effectively control the charges in the channel and body regions. IG has an asymmetric structure with an underlap (Lunderlap) region to reduce the Shockl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Trapped electrons increase the potential barrier, impeding electron flow. As a result, the sensing margin and retention time reach their minimum values of 24.51 μA μm −1 and 1.991 s, respectively, in the 1 13) 14.10 251 2 27) 1.11 120 3 28) 0.39 10 4 29) 2.51 598 5 30) 8.73 704 6 31) 422 120 7 32) 12 170 8 33) 0. D-D′ case.…”
Section: Effect Of the Variable Gb Locationmentioning
confidence: 97%
“…Trapped electrons increase the potential barrier, impeding electron flow. As a result, the sensing margin and retention time reach their minimum values of 24.51 μA μm −1 and 1.991 s, respectively, in the 1 13) 14.10 251 2 27) 1.11 120 3 28) 0.39 10 4 29) 2.51 598 5 30) 8.73 704 6 31) 422 120 7 32) 12 170 8 33) 0. D-D′ case.…”
Section: Effect Of the Variable Gb Locationmentioning
confidence: 97%
“…Note that most 1T-DRAMs store holes in the body region near the metal gate. [20][21][22][23][24][25] However, the proposed JL bulk-FinFETbased 1T-DRAM device stores holes in H body-fin rather than H fin , as shown in Fig. 5(a).…”
Section: Effect Of Wfv On Memory Performancesmentioning
confidence: 99%
“…This side effect is one of the critical issues encountered in the implementation of the HK/MG technology, and it not only affects logic transistors but also influences memory transistors. [20][21][22][23][24][25] So far, a few studies on WFV have been reported in the literature; [12][13][14][15][16][17][18][19] however, the impact of WFV on memory characteristics is yet to be investigated. Recently, Lee et al studied and investigated the effect of WFV on the transfer characteristics and memory performance of a gate-all-around junctionless (JL) field-effect transistor-based capacitorless dynamic random-access memory (1T-DRAM).…”
Section: Introductionmentioning
confidence: 99%
“…SOI-like structures can be fabricated using polycrystalline silicon, but its grain boundaries affect the transfer characteristics and memory performance of such structures. [13][14][15][16] To address this issue, a junctionless bulk fin-type field-effect transistor (FinFET)-based (JLBF) 1T-DRAM was proposed herein that does not require a SOI or SOI-like structure. The proposed 1T-DRAM was fabricated by changing only the doping type of a typical junctionless bulk FinFET.…”
Section: Introductionmentioning
confidence: 99%